Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - Chapter Review Exercises - Page 164: 57


$$ G'(2)= -18.$$

Work Step by Step

Given $ F(x)=f(g(2x))$, then we have $ G'(x)=2f'(g(2x))g'(2x)$ and hence $$ G'(2)=2f'(g(4))g'(4)=2f'(2) (3)=6(-3)=-18.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.